Argatroban administration reduces leukocyte adhesion and improves capillary perfusion within the intestinal microcirculation in experimental sepsis - Fuchs, Christian; Ladwig, Elena; Zhou, Juan; Pavlovic, Dragan; Behrend, Kristina; Whynot, Sara; Hung, Orlando; Murphy, Michael; Cerny, Vladimir; Lehmann, Christian (Thrombosis and Haemostasis, 2010)
Co-activation of pro-coagulatory pathways in sepsis may result in disseminated intravascular coagulation and contributes to microvascular dysfunction. We investigated the effects of the direct thrombin inhibitor, argatroban (ARG), on the sepsis-induced impairment of the intestinal microcirculation (capillary perfusion, leukocyte adhesion) and the vascular contractility in rats. Forty male Lewis rats were randomly assigned to one of four groups: sham surgery (SHAM), experimental sepsis (colon ascendens stent peritonitis – CASP), CASP+ARG, and SHAM+ARG. At 16 hours after colon stent insertion (or sham surgery), 2 mg/kg argatroban or buffer were given intravenously, and 1 hour thereafter, intravital microscopy was performed. In addition, experiments to study the impact of ARG on vascular contractility were conducted in vitro. ARG administration in CASP rats significantly increased functional capillary density in mucosal (+128%) and muscular layers (longitudinal: +42%; circular: +64%) and decreased the number of firmly adhering leukocytes in the intestinal submucosa compared to untreated animals. In vitro findings indicated a vasodilating effect of ARG. ARG administration during experimental sepsis improved intestinal microcirculation by preserving functional capillary density, an indicator of microvascular perfusion, and by reducing leukocyte adherence to the endothelium in submucosal venules.
Keywords: Inflammation; argatroban; sepsis; leukocytes; microcirculation